PENYULUHAN HUKUM TENTANG DAMPAK PIDANA PENYALAHGUNAAN MEDIA SOSIAL DI KALANGAN SISWA SMAN 5 KOTA SERANG - Tituk Yuana Widiyati; Sri Lidya Agustin; Anita Fitri; Andre Trizalna (PT. Hasba Edukasi Mandiri, 2026)
The proliferation of social media among students has given rise to various problems, such as the spread of hoaxes, cyberbullying, hate speech, and defamation, all of which can have legal consequences. Students' lack of understanding of the legal limitations of social media use is one of the causes of social media misuse among students. Therefore, this Community Service (PKM) activity aims to increase students' understanding and legal awareness regarding the criminal consequences of social media misuse. The activity was held at SMAN 5 Kota Serang on April 27, 2026, using legal counseling, discussions, questions and answers, and case studies. The results showed an increase in students' understanding and legal awareness regarding the wise and responsible use of social media. Students gained a better understanding of legal limitations, criminal consequences, and the importance of ethics in social media. Furthermore, low digital legal education and digital literacy skills remain contributing factors to the suboptimal use of social media. Therefore, this legal counseling is effective in increasing students' legal knowledge and awareness, necessitating ongoing legal education activities within the school environment.